Neuroprotective effect of bromelain on BDNF-TRKB signalling pathway in chronic unpredictable stress-induced depression model - Rajeshwari Parasuraman; Dheepthi Jayamurali; Nivedita Manoharan; Sathya Narayanan Govindarajalu (Beni-Suef University Journal of Basic and Applied Sciences, 2024)
Abstract Background Bromelain is a mixture of protease enzyme extract from the fruit or stem of the pineapple plant. It has a wide range of biological actions, and it is most commonly used as an anti-inflammatory agent. This study was designed to investigate the antidepressant effect of bromelain on chronic unpredictable stress (CUS)-induced depression in rat models by targeting various molecular mechanisms. Result We studied the in silico analysis of the antidepressant potential of bromelain by docking with various proteins involved in the pathophysiology of depression. As a result of in silico studies, bromelain showed good binding energy with IL1β, 5-HT, BDNF, CREB, and TrkB. The mRNA expression of BDNF, TrkB, AKT, ERK, and IL-1β was studied by qRT-PCR. Gene expression studies showed a significant decrease in BDNF, TrkB, AKT, and ERK in chronic unpredictable stress, whereas there was a significant increase in the case of the bromelain- and fluoxetine-treated group. Since neuroinflammation is also one of the major concerns in the pathophysiology of depression, pro-inflammatory cytokines were also studied along with apoptotic markers using ELISA. ELISA results showed a significant increase in inflammatory cytokines in CUS, and it was significantly decreased in the case of the bromelain- and fluoxetine-treated group. Similarly, there was an increased concentration of pro-apoptotic protein in the CUS group, whereas it was decreased in the bromelain and fluoxetine groups. Conclusions From the results, it is clear that bromelain exerts an antidepressive effect by preventing neuroinflammation and neurodegeneration and by enhancing neurogenesis and neuroplasticity. Graphical abstract